Spatial heuristics and random spatial exploration: children, adults, and the machine coloring-in places in the grid game - Lange-Küttner, Christiane; Beringer, Jörg (Frontiers in Developmental Psychology, 2025)
IntroductionThis study investigates the long-standing Research Topic of the development of the space concept in children using a competitive, interactive, online, zero-sum game that required players, taking turns with a computer player, to use monochromatic electronic paint to complete coloring in places until an entire 10 × 10 grid was filled.MethodsChildren were 4- to 5-year-olds (n = 26), 6- to 7-year-olds (n = 32), 8- to 10-year-olds (n = 52), as well as adults (n = 48). The total sample consisted of 79 human and 79 machine players (N = 158). The human players colored in places on the grid in yellow, and the machine player in green. While human players could follow their own spatial heuristics, the machine system player was programmed to randomly color in anywhere in the grid. Neighboring places could visually merge into pathways or areas.ResultsChildren explored the array somewhat less than adults, but both explored it less than the machine, which randomly colored in places across the entire array. Both children and adults as well as the machine players created one large area and many smaller ones. Their one large area left a large swath of the spatial array empty. This space was then filled in by the machine player at random places, which merged into a slightly smaller large area or many larger small areas.DiscussionHence, a similar outcome was achieved regardless of whether spatial concepts or random spatial explorations were devised. The use of spatial heuristics was demonstrated with correlational analyses, where long pathways and short-distance moves were significantly correlated with the largest area, but not in their machine opponents.